Indirect effects on fitness between individuals that have never met via an extended phenotype. (10th February 2019) - Fisher, David N.; Haines, Jessica A.; Boutin, Stan; Dantzer, Ben; Lane, Jeffrey E.; Coltman, David W.; McAdam, Andrew G.
Abstract: Interactions between organisms are ubiquitous and have important consequences for phenotypes and fitness. Individuals can even influence those they never meet, if they have extended phenotypes that alter the environments others experience. North American red squirrels ( Tamiasciurus hudsonicus ) guard food hoards, an extended phenotype that typically outlives the individual and is usually subsequently acquired by non‐relatives. Hoarding by previous owners can, therefore, influence subsequent owners. We found that red squirrels breed earlier and had higher lifetime fitness if the previous hoard owner was a male. This was driven by hoarding behaviour, as males and mid‐aged squirrels had the largest hoards, and these effects persisted across owners, such that if the previous owner was male or died in mid‐age, subsequent occupants had larger hoards. Individuals can, therefore, influence each other's resource‐dependent traits and fitness without ever meeting, such that the past can influence contemporary population dynamics through extended phenotypes.